Study of the resilience index for steel moment frames with reversible connections. (January 2023) - Bavandi, Mohammad; Ghodrati Amiri, Gholamreza; Rajabi, Elham; Moghadam, Abdolreza S.
Abstract: Natural hazards can turn into crises with dangerous consequences in the absence of hazards reduction systems. Estimation of hazards quantitatively can lead to the prevention of these crises. Structural resilience is divided into different dimensions of social, economic, organizational, technical, etc. Qualitatively, it means predicting a set of factors in the shortest possible time to return the damaged structure to its former performance. In this study, due to the quantitative concept of vulnerability to reduce the direct economic hazards of the structure, six models of 3-story buildings with post-tensioned self-centering connections have been evaluated for resilience according to the damage curve. Based on Incremental Dynamic Analysis (IDA) and considering five scenarios with the onset times of various events, a new seismic resilience index has been developed based on the vulnerability curve for post-tensioned self-centering buildings. Another quantitative index has been proposed for rapid assessment of self-centering structures due to the importance of four different hazard levels of 2 %, 5 %, 10 %, and 20 % in 50 years and the prediction of various event times. One of the important results of this research is the reduction of resilience and structural performance due to the increase in the occurred event times. If these indices were closer to 100 %, the resilience of buildings would be higher.